Fun Science in the Classroom: Collaboration of PGSD Alum Students in Creating Interactive Media for SD Negeri 8 Juli - Dwi Adhinda Junaidi Putri; Erlia Hanum; Friantiani Safitri (STMIK Indonesia Banda Aceh, 2025)
This study aims to describe the process and impact of collaboration between students of the Primary School Teacher Education (PGSD) Study Program and SD Negeri 8 Juli in creating interactive science-based learning media for science education. This activity was conducted within the context of the Science Media Product course, using a descriptive qualitative approach and a case study method. The research subjects included sixth-semester PGSD students, fourth-grade teachers, and fourth-grade students. Data collection techniques consisted of observation, interviews, and documentation. The results showed that the collaboration produced educational videos and learning games that enhanced student engagement, facilitated the understanding of science concepts, and created a fun learning atmosphere. The students also gained reflective experience in understanding learners’ needs and developing pedagogical creativity. This activity serves as a concrete form of project-based learning and field practice aligned with the Merdeka Curriculum policy. The study recommends strengthening campus-school partnerships to support learning innovation and the development of pre-service teacher competencies.